PENGEMBANGAN SUMBER BELAJAR BERMAIN BERBASIS MOBILE LEARNING - Yenti Juniarti; Eva Gustiana (Jurnal Pendidikan Edutama, 2019)
Abstract: This research aims to develop learning resources for playing subjects. The development of learning resources produces products in the form of play applications that are packaged in the form of * apk that can be installed in mobile phone an-based Android. The research method used is research and development methods with development steps designed by Dick & Carry. The subjects of this study were students of early childhood education who had 35 subjects. Based on data analysis needs obtained 100% results of students need the development of this learning resource. Whereas according to the results of expert play evaluation obtained an average score of 3.58 (very good) with a percentage of 89.44%, according to learning technology experts obtained an average score of 3.56 (very good) with a percentage of 89.34 %, learning experts obtained an average score of 3.67 (very good) with a percentage of 91.67%. The trial results of small groups obtained an average score of 3.26 (good) with a percentage of 80.09%, while the results of the large group trial obtained an average score of 3.57 (very good) with a percentage of 87.96%. Keywords: Learning Resources, Playing, Mobile Learning Abstrak: Penelitian ini bertujuan untuk mengembangkan sumber belajar matakuliah bermain. Pengembangan sumber belajar ini menghasilkan produk berupa aplikasi bermain yang dikemas dalam bentuk *apk yang bisa di install dalam handphone berbasis android. Metode penelitian yang digunakan adalah metode penelitian dan pengembangan dengan langkah-langkah pengembangan yang dirancang oleh Dick & Carry. Subjek dari penelitian ini adalah mahasiswa Pendidikan anak usia dini yang telah memperoleh mata kuliah bermain sebanyak 35 mahasiswa. Berdasarkan data analisis kebutuhan diperoleh hasil 100% mahasiswa membutuhkan pengembangan sumber belajar ini. Sedangkan menurut hasil evaluasi ahli bermain diperoleh rata-rata skor sebesar 3,58 (sangat baik) dengan persentase sebesar 89,44%, menurut ahli teknologi pembelajaran diperoleh rata-rata skor sebesar 3,56 (sangat baik) dengan persentase sebesar 89,34%, ahli pembelajaran diperoleh rata-rata skor sebesar 3,67 (sangat baik) dengan persentasenya 91,67%. Hasil uji coba kelompok kecil memperoleh rata-rata skor 3,26 (baik) dengan persentase 80,09%, sedangkan hasil uji coba kelompok besar diperoleh rata-rata skor sebesar 3,57 (sangat baik) dengan persentase 87,96%. Kata kunci: Sumber Belajar, Bermain, Mobile Learning